Peningkatkan Hasil Belajar IPA melalui Model Pembelajaran Mind Mapping di SDN Ciater 03 Tangerang Selatan - Elma Silvia (Program Studi PGSD Universitas Flores, 2020)
The background of this study is many students’ learning outcomes less than minimal completeness criteria. The purpose of this study is to improve science learning outcomes of students on the material Outer Shape of Animal’s Body and Plant and Its Function through Mind Mapping Learning Model in class IV students. The research method used was Classroom Action Research that followed the Kemmis & Taggart model. This study includes 3 cycles; each cycle includes 4 stages, namely planning, acting, observing and reflecting. The results showed that there was a significant increase in science learning outcomes in grade IV students. It can be proved through the average results of natural science tests in each cycle that always increases. The average value achieved in cycle I = 70.30; cycle II= 77.91; and cycle III = 80.09. The results of the interview can be concluded that learning science through Mind Mapping is fun for students. Thus it can be concluded overall that learning science using Mind Mapping method can improve students’ learning outcomes in science.